Factores de riesgo modificables a desarrollar enfermedades crónicas no transmisibles en Choferes de la Cooperativa de Transportes Loja con sobrepeso y obesidad - Campoverde Chamba, Cinthya Karina (2019)
Overweight and obesity are a global pandemic and are associated with increasing chronic processes. The specific objectives of the study were: estimate the prevalence of overweight and obesity through body mass index (BMI), age and genre; identify modifiable risk factors associated with developing chronic noncommunicable diseases (NCDs) with overweight and degrees of obesity and; establish the relationship between modifiable risk factors with chronic noncommunicable diseases in overweight and obese drivers of the "Cooperativa de Transportes Loja". The study was descriptive, transversal with quantitative approach, with a sample of 92 drivers between 40 and 65 years and, through the BMI were identified overweight and obese drivers to whom the survey was applied investigating consumption of tobacco products, alcohol, inadequate diet, and physical inactivity. The result was that 41,30% of drivers were overweight and 44,57% obese, being greater overweight in the group between 40-45 years. The most frequent risk factor was physical inactivity with 35,44% and 25,32% for overweight and obese drivers respectively. Through Odds Ratio (OR) was determined to inadequate diet and alcohol consumption constitute a 3 times higher risk to develop chronic noncommunicable diseases. On the basis of the above, it was concluded that 8 out of 10 drivers had altered nutritional status and presented as main risk factors physical inactivity and inadequate diet to develop NCDs. Keywords: tobacco, alcohol, physical inactivity, diet